KARAKTER BERTANGGUNG JAWAB DALAM PERMAINAN UCING SUMPUT SISWA SEKOLAH DASAR DI KAMPUNG PASIRMULYA KECAMATAN PANGALENGAN - Ismail, Kamal (Al-Mubtadi: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This article provides an overview of Ucing Sumput in the character of responsibility. The scope of this article contains the definition, structure and activities of Ucing Sumput. The methods used in writing this article are literature review and field observation in Pasirmulya Village. The result of this study is a description of the acquisition of responsible character through Ucing Sumput, then the use of this paper becomes a reference in the development of responsible character research.